1972
DOI: 10.1037/h0033366
|View full text |Cite
|
Sign up to set email alerts
|

Elation, depression, and helping behavior.

Abstract: p < .05. **p < .001. Note.-Cells which share a common subscript are not significantly different from each other at the .05 level hy the Newman-Keuls test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(73 citation statements)
references
References 7 publications
(11 reference statements)
7
65
0
1
Order By: Relevance
“…In an experimental context, induced positive moods have been shown to bring about helping in a variety of forms, including making a charitable contribution (Cunningham, Steinberg, & Grev, 1980;Isen, 1970), sharing with others (Rosenhan, Underwood, & Moore, 1974), donating blood (O'Malley & Andrews, 1983), or volunteering one's time (Aderman, 1972;Baron & Bronfen, 1994;Baron et al, 1992;Berkowitz, 1987;Isen & Levin, 1972;Rosenhan, Salovey, & Hargis, 1981). Such evidence bodes well for happy employees and corroborates the crosssectional evidence that they are more likely to help others in a work context.…”
Section: Experimental Evidence: Does Happiness Lead To Success In Thesupporting
confidence: 61%
“…In an experimental context, induced positive moods have been shown to bring about helping in a variety of forms, including making a charitable contribution (Cunningham, Steinberg, & Grev, 1980;Isen, 1970), sharing with others (Rosenhan, Underwood, & Moore, 1974), donating blood (O'Malley & Andrews, 1983), or volunteering one's time (Aderman, 1972;Baron & Bronfen, 1994;Baron et al, 1992;Berkowitz, 1987;Isen & Levin, 1972;Rosenhan, Salovey, & Hargis, 1981). Such evidence bodes well for happy employees and corroborates the crosssectional evidence that they are more likely to help others in a work context.…”
Section: Experimental Evidence: Does Happiness Lead To Success In Thesupporting
confidence: 61%
“…Some studies are able to address this question directly, as they include both positive affect and negative affect as variables or manipulations. For example, in the helping literature, experimental inductions of positive affect produce increased prosocial behavior, whereas inductions of negative affect do not necessarily decrease helping (e.g., Aderman, 1972;Berkowitz, 1987;Isen & Levin, 1972;Rosenhan et al, 1974). Regarding social interactions (e.g., Cunningham, 1988aCunningham, , 1988b, creativity (e.g., Hirt et al, 1996;Richards, 1994), and evaluations of strangers (e.g., Baron, 1987Baron, , 1993, it appears that positive mood inductions do not produce symmetrical effects.…”
Section: Causality and Possible Third Variablesmentioning
confidence: 99%
“…Both the inductions of positive mood and the assessments of helping have taken numerous forms in these studies. For example, happy moods, in comparison with sad or neutral moods, have promoted such behaviors as contributing money to charity (Cunningham, Steinberg, & Grev, 1980;Isen, 1970) or to needy children (Rosenhan, Underwood, & Moore, 1974), donating blood (O'Malley & Andrews, 1983), and volunteering for an extra experiment (Aderman, 1972;Baron & Bronfen, 1994;Baron et al, 1992;Berkowitz, 1987;Isen & Levin, 1972;Rosenhan, Salovey, & Hargis, 1981).…”
Section: Prosocial Behaviormentioning
confidence: 99%
“…This relationship has been well-documented through correlational methods (Aderman, 1972;Cunningham, Steinberg, & Grev, 1980;Lucas, 2001;Rosenhan, Underwood, & Moore, 1974;Williams & Shiaw, 1999) and, more recently, with experimental design (Lyubomirsky, Sheldon, & Schkade, 2005). For example, Lyubomirsky and colleagues showed that students assigned to perform five random acts of kindness a week for 6 weeks were happier than those in a no-action control group.…”
Section: The Relationship Between Money and Happinessmentioning
confidence: 99%